The Gains/Losses of Canadian Religious Groups from Immigration: Immigration Flows, Attendance and Switching - Reimer, Samuel Harold (Studies in religion, 2018)
Immigration is changing the religious landscape in Canada. It is estimated that 69% of the Canadian population growth is accounted for by immigration, and this is expected to increase to 90% in 2050. In addition, immigrants participate in institutional religion at higher rates than the Canadian-born. While the Muslim, Hindu, Sikh, and Buddhist populations are growing rapidly due to immigration, nearly half of all immigrants claim some type of Christian affiliation. There are also many non-religious immigrants. In this article, we look at the growth and decline of immigration flows, service attendance, and switching/retention to show which religious groups in Canada are benefitting from immigration.